The Growing and Evolving Business of Private Participation in Airports : New Trends, New Actors Emerging - Andrew, Doug (World Bank, Washington, DC, 2012)
Private sector management and financing of airports has continued to expand in developing countries. Long-term concessions for airports are the predominant model today, with governments often taking a minority shareholding in the venture. Careful attention to policy design, regulatory issues, and management of concessions will continue to be important in ensuring that private participation delivers efficient and effective airport infrastructure services.